Social Media: Research on Changing the Roles of Journalists - Safori, Amjad Omar (Journal of New Media and Mass Communication, 2018)
The impact of rise in the use of social media on the journalism and on various positions within the industry has been discussed by several researchers. However, contemporary studies do not provide any significant qualitative research related to the impression of journalist interaction with social media. The current study is focused on the opinions of the Jordanian journalist about how the social media has affected their profession and role in journalism. Several interviews are conducted that provide an insight on the journalist perception related to the interaction with the reader. Audience interaction, rise of personalized journalism and preferences of the journalists related to social media are investigated in this study. The investigation provides contrasting views. A result validates the drastic impact of social media on profession with some participants supporting that social media has helped in advancement in their profession, and others consider it as interference in their professional role.